Subjects of politics: Between democracy and dictatorship in Thailand. (March 2019) - Elinoff, Eli
In May of 2014, the Thai military deposed elected Prime Minister Yingluck Shinawatra. Since the coup, the chief aim of the military government has been to bring order to the country by silencing politics. In this paper, I trace the drift from democracy to dictatorship as a set of disagreements about democracy and its redistribution of political capacity. Specifically, I show how debates revolving around the political capacities of the poor reflect both the emergence of a new subject of politics and the anxieties produced by shifting arrangements of the political. 1 Working from the vantage point of urban railway squatter communities in northeastern Thailand, I show how disagreements between residents, non-governmental organization activists, state development agencies and the military reflect unresolved tensions between multiple orderings of the political and the unreconciled question of who is a legitimate political actor. Residents' engagements with development projects preceding the coup expose the ways in which their emergent claims to political capacity provoked new governmental strategies to incorporate their voices but manage their political aspirations. Military rule has once again transformed the shape of the political, narrowing the horizons of political possibility for citizens such as those living along the railway tracks. Yet, even amidst such threats, the military government remains fragile precisely because the political is always contingent, composed of heterogeneous disagreements. By making these processes legible through an ethnography of disagreement, I argue that anthropology and ethnography are fundamental for understanding the emerging forms of the political in the 21st century.